DEVELOPMENT OF GROUND ENVIRONMENT IMPROVEMENT AND RESTORATION USING THE ROTARY CRUSHING AND DIFFUSIVE MIXING METHOD AS WELL AS ION ADSORPTION METHOD - Mutsuhiro Ohno; Noriaki Nakajima; Hideo Suhara; Yuichiro Mishima; Hiroyuki Araki (International Association of Lowland Technology, 2014)
Lowlands are easily concentrated by effects of water and soil pollution. There is a demand for the development of technology that can both restore the ground environment and improve soft ground. The authors implemented testing used a rotary crushing and diffusive mixing (referred to hereafter as RCDM) method and an ion adsorption method (Nano-size inorganic Layered Double Hydroxide - NLDH - method) for the purpose of developing technology that can restore the ground environment and improve soft ground. These examples are believed to show the broad applicability of both methods.